Interaction potentials between atoms and cryogenic surfaces - Nguyen, Hong Nhung (2015)
For interfacing atomic systems with solid state systems the atom surface interaction plays an important role. In certain systems the interaction depends strongly on the temperature and atoms can be trapped on cryogenic surfaces by forming atom surface bound states. In this project we estimate numerically the energies of bound states in the trapping potential by solving the associated Schrodinger equation. We then investigate experimentally these bound states between Rubidium and a Sapphire surface with absorption spectroscopy and evanescent wave spectroscopy. The spectrum can be used to determine the trapping potential.